The Women’s Empowerment in Agriculture Index - Alkire, Sabina; Meinzen-Dick, Ruth S.; Peterman, Amber; Quisumbing, Agnes R.; Seymour, Greg; Vaz, Ana (International Food Policy Research Institute, 2012)
The Women’s Empowerment in Agriculture Index (WEAI) is a new survey-based index designed to measure the empowerment, agency, and inclusion of women in the agricultural sector. The WEAI was initially developed as a tool to reflect women’s empowerment that may result from the United States government’s Feed the Future Initiative, which commissioned the development of the WEAI. The WEAI can also be used more generally to assess the state of empowerment and gender parity in agriculture, to identify key areas in which empowerment needs to be strengthened, and to track progress over time.